Giant fine structure splitting of the bright exciton in a bulk MAPbBr3 single crystal - Baranowski, M; Galkowski, K; Surrente, A; Urban, JM; Klopotowski, Ł; Mackowski, S; Maude, DK; Aich, R; Boujdaria, K; Chamarro, M; Testelin, C; Nayak, P; et al. (American Chemical Society, 2019)
Exciton fine structure splitting in semiconductors reflects the underlying symmetry of the crystal and quantum confinement. Since the latter factor strongly enhances the exchange interaction, most work has focused on nanostructures. Here, we report on the first observation of the bright exciton fine structure splitting in a bulk semiconductor crystal, where the impact of quantum confinement can be specifically excluded, giving access to the intrinsic properties of the material. Detailed investigation of the exciton photoluminescence and reflection spectra of a bulk methylammonium lead tribromide single crystal reveals a zero magnetic field splitting as large as ~200μeV. This result provides an important starting point for the discussion of the origin of the large bright exciton fine structure observed in perovskite nanocrystals.